Histologic transformation in lung cancer: when one door shuts, another opens. (October 2022) - Sato, Yuki; Saito, Go; Fujimoto, Daichi
Histologic transformation (HT) is a major cause of drug resistance to therapy in patients with lung cancer. HTs to small-cell lung cancer (SCLC) have been reported frequently in patients with epidermal growth factor receptor ( EGFR )-mutated lung cancer. Although HTs have an impact on the clinical outcomes in patients owing to a high refractoriness to treatments, there is limited data on the prevalence, causes, mechanisms, treatment efficacy, and future treatment strategies. In this review, we assess the literature regarding HTs comprehensively, including those describing EGFR-tyrosine kinase inhibitors, other molecular targeted drugs, and immune checkpoint inhibitors. Furthermore, we discuss the mechanisms of HTs and the lineage plasticity to SCLC and squamous cell carcinoma in lung cancer. In addition, we summarize the treatment efficacy and future perspectives of HTs in patients with lung cancer, and propose better management strategies for this group of patients.